Recent changes in winter Arctic clouds and their relationships with sea ice and atmospheric conditions - Sang-Yoon Jun; Chang-Hoi Ho; Jee-Hoon Jeong; Yong-Sang Choi; Baek-Min Kim (Tellus: Series A, Dynamic Meteorology and Oceanography, 2016)
Changes in Arctic clouds during boreal winter (December through February) and their relationship with sea ice and atmospheric conditions in recent decades have been examined using satellite and reanalysis data, and they are compared with output data from atmospheric general circulation model (AGCM) experiments. All the datasets used in this study consistently show that cloud amount over the Arctic Ocean (north of 67°N) decreased until the late 1990s but rapidly increased thereafter. Cloud increase in recent decade was a salient feature in the lower troposphere over a large part of the Arctic Sea, in association with obvious increase of lower tropospheric temperature and moisture. The comparison between the two periods before and after 1997 indicates that interannual covariability of Arctic clouds and lower tropospheric temperature and moisture was significantly enhanced after the late 1990s. Large reduction of sea ice cover during boreal winter decreased lower tropospheric static stability and deepened the planetary boundary layer. These changes led to an enhanced upward moisture transport and cloud formation, which led to considerable longwave radiative forcing and, as a result, strengthened the cloud–moisture–temperature relationship in the lower troposphere. AGCM experiments under reduced sea ice conditions support those results obtained by satellite and reanalysis datasets reproducing the increases in cloud amount and lower tropospheric temperature and their enhanced covariability.